Maternal or zygotic sphingosine kinase is required to regulate zebrafish cardiogenesis. Issue 8 (6th July 2015) - Mendelson, Karen; Lan, Yahui; Hla, Timothy; Evans, Todd
ABSTRACT: Background: The sphingosine 1‐phosphate (S1P) signaling pathway regulates zebrafish cardiogenesis, and provides a paradigm for how signaling gradients coordinate collective cell migration across tissue layers. It is known that the S1P transporter (Spns2) functions in extra‐embryonic YSL to activate G protein–coupled receptor (S1pr2) signaling in endoderm for deposition of positional cues (integrin, fibronectin, etc.). Such cues are recognized by overlying lateral precardiac mesoderm that migrates to the midline and fuses to form the primordial heart tube. However, the source of bio‐active S1P is not known. There are multiple receptors and it is not known if there are earlier or even receptor‐independent functions for S1P. Results: Because S1P can only be generated by sphingosine kinases, we targeted a mutation to the single kinase gene expressed during early embryogenesis ( sphk2 ). Zygotic mutants survive to adulthood and appear normal, but maternal‐zygotic mutant embryos phenocopy null zygotic mutants of spns2 or s1pr2 . Conclusions: The data show that maternally derived sphk2 RNA is fully sufficient to generate an S1P signaling gradient in the YSL that ultimately controls precardiac mesoderm migration during embryogenesis. Furthermore, despite maternal expression of sphk2, there are no obvious developmental functions requiring its activity prior to stimulation of S1pr2 in endoderm. Developmental Dynamics 244:948–954, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: A single sphingosine kinase is expressed during early embryogenesis. A mutant was targeted to block kinase activity. Zygotic homozygous mutants appear normal. Maternal‐zygotic mutants phenotype mil and spns2 mutants.